Detection and evaluation of intron retention events in the human transcriptome - GALANTE, PEDRO ALEXANDRE FAVORETTO (Copyright 2004 by RNA Society, 2004)
Alternative splicing is a very frequent phenomenon in the human transcriptome. There are four major types of alternative splicing: exon skipping, alternative 3′ splice site, alternative 5′ splice site, and intron retention. Here we present a large-scale analysis of intron retention in a set of 21,106 known human genes. We observed that 14.8% of these genes showed evidence of at least one intron retention event. Most of the events are located within the untranslated regions (UTRs) of human transcripts. For those retained introns interrupting the coding region, the GC content, codon usage, and the frequency of stop codons suggest that these sequences are under selection for coding potential. Furthermore, 26% of the introns within the coding region participate in the coding of a protein domain. A comparison with mouse shows that at least 22% of all informative examples of retained introns in human are also present in the mouse transcriptome. We discuss that the data we present suggest that a significant fraction of the observed events is not spurious and might reflect biological significance. The analyses also allowed us to generate a reliable set of intron retention events that can be used for the identification of splicing regulatory elements.